Dietary Supplementation of Choline or Potassium in Low Crude Protein Diets on Growth and Carcass Performance of Finishing Pigs from 245 to 295 lb - J. Soto; M. D. Tokach; S. S. Dritz; J. C. Woodworth; J. M. DeRouchey; R. D. Goodband (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 284 pigs (DNA 600 × 241, initially 247.4 lb) were used in a 26-d trial to determine the effect of added choline or potassium on growth and carcass performance of finishing pigs fed low CP diets. Pens of 7 or 8 pigs were allotted by BW and randomly assigned to 1 of 4 dietary treatments with 9 replications per treatment. Experimental treatments included a 12% CP, positive control diet with 10.6% SBM; a 10% CP, negative control diet with 4.0% SBM; the negative control with added choline; or potassium such that the added choline or potassium matched the amount that was provided in the 12% CP diet. At d 26, pigs were transported to a packing plant for processing and carcass data collection. For overall growth performance, there was no evidence for differences in ADG or ADFI; however, there was a marginal improvement (P<0.10) in F/G for pigs fed the positive control diet with 12% CP compared with the mean of pigs fed the diets with 10% CP. Adding choline or potassium to the diet did not influence performance. For carcass characteristics, there was no evidence for differences in HCW, yield, backfat, loin depth, or lean percentage. In summary, marginally poorer F/G observed in pigs fed the 10% CP diet with 4.0% SBM was not influenced by supplementation with choline or potassium.
Keywords: soybean meal; crude protein; finishing pigs